Anaerobic digestion beyond biogas. (October 2021) - Kumar Khanal, Samir; Lü, Fan; Wong, Jonathan W.C.; Wu, Di; Oechsner, Hans
Abstract: Anaerobic digestion (AD) is a matured technology for waste (water) remediation/stabilization and bioenergy generation in the form of biogas. AD technology has several inherent benefits ranging from generating renewable energy, remediating waste (water), and reducing greenhouse gas emission to improving health/hygiene and the overall socio-economic status of rural communities in developing nations. In recent years, there has been a paradigm shift in applications of AD technology beyond biogas. This special issue (SI) entitled, " Anaerobic Digestion Beyond Biogas (ADBB-2021), " was conceptualized to incorporate some of the recent advances in AD in which the emphasis is beyond biogas, such as anaerobic biorefinery, chain elongation, treatment of micropollutants, toxicity and system stability, digestate as biofertilizer, bio-electrochemical systems, innovative bioreactors, carbon sequestration, biogas upgrading, microbiomes, waste (water) remediation, residues/waste pre-treatment, promoter addition, and modeling, process control, and automation, among others. This VSI: ADBB-2021 contains 53 manuscripts (14 critical reviews and 39 research). The key findings of each manuscript are briefly summarized here, which can serve as a valuable resource for AD researchers to learn of major advances in AD technology and identify future research directions.